Only baseline amyloid burdens and their incremental change could not predict AD progression in mild cognitive impairment. (1st February 2022) - Choo, Il Han; Chong, Ari; Chung, Ji Yeon; Ha, Jung‐Min; Choi, Yu Yong; Kim, Hoowon
Abstract: Background: Mild cognitive impairment (MCI) is the intermediate stage between cognitively normal and dementia. Cerebral amyloid burden by amyloid PET is the pathological biomarker of Alzheimer's disease (AD). The goal of this study was to evaluate the prognostic ability of baseline amyloid burdens and their incremental change in the MCI participants. Method: Seventy‐two MCI participants were selected in this study by inclusion and exclusion criteria. They underwent baseline and annual follow‐up evaluation including comprehensive neuropsychological assessment, consensus clinical diagnosis for 2 years. The [18F]Florbetaben PET and MRI scans were also performed. T1‐weighted MR 3D volumes were acquired for co‐registration with PET. Dichotomous categorization was performed for baseline β‐amyloid (Aβ) positivity by mean cortical amyloid burden cut‐off score. And annual amyloid burden changes were also acquired. Result: Baseline Aβ positivity evaluation defined 36 Aβ positive (Aβ+ve) and 36 Aβ negative (Aβ‐ve) MCI individuals. Of 36 Aβ+ve MCI subjects, 9 MCI progressed to AD and of 36 Aβ‐ve MCI subjects, 7 MCI progressed to AD (p = 0.280). MCI subjects with amyloid burden increase were 4 of 16 AD converters and 22 of 56 non‐converters (stable MCI) (p = 0.294). Conclusion: Our results suggest that only baseline MCI amyloid burdens and their incremental change could not predict AD progression.